Development of ternary-component mixed-matrix membranes for advanced gas separations - Samarasinghe, Samarasinghe Arachchige Sulashi Chathushka (Nanyang Technological University, 2020)
Polymer-based mixed-matrix nanocomposites are increasingly researched as gas separation membranes. In contrast to the conventional single-filler mixed-matrix membranes (MMMs), here in this thesis study, I examined the utility of ternary-component MMMs for gas separation applications. The strategy employed in this thesis was to develop Matrimid-based MMMs using filler and a polymeric compatibilizer. As the filler, I selected a well-known oxygen carrier, cobalt phthalocyanine. As the compatibilizer, I employed a block copolymer, Pluronic F-127. The ternary-component membrane exhibited 64% improvement in O2 permeability and 40% improvement in O2/N2 selectivity. To improve the selectivity, I focused on a high-permeability polymer, ODPA-TMPDA, as the next step. The filler (cobalt (III) acetylacetonate) successfully improved the selectivity but at the cost of permeability. Thus, I examined a porous covalent organic framework, SNW-1, together with cobalt (III) acetylacetonate as the next step. This strategy improved both O2 permeability and O2/N2 selectivity. Due to the success of ODPATMPDA- based ternary-component membrane for O2/N2 separation, I have used ODPA-TMPDA for the development of another ternary-component membrane for CO2/CH4 separation. In this final step of the thesis work, I have incorporated 2D CuBDC nanosheets and 3D ZIF-8 nanoparticles to improve CO2/CH4 selectivity and CO2 permeability, respectively. Overall, this study demonstrates the potential of ternary-component MMMs for developing gas separation membranes that can surmount Robeson’s Upper Bound relation for permeability-selectivity trade-off.